2020
DOI: 10.1155/2020/8820296
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fluid Pressure Wave between Biot Theory and Storativity Equation

Abstract: Compressibilities of pore fluid and rock skeleton affect pressure profile and flow velocity of fluid in aquifers. Storativity equation is often used to characterize such effects. The equation suffers from a disadvantage that at infinite large frequency, the predicted velocity of fluid pressure wave is infinitely large, which is unrealistic because any physical processes need certain amounts of time. In this paper, Biot theory is employed to investigate the problem. It is shown that the key equations of Biot th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…The elastic model in the Appendix has two assumptions: (1) the rocks are undrained during the passage of a transient Rayleigh wave such that the Gassmann (1951) equation is applicable; (2) the well head adequately represents fluid pressure in the matrix surrounding the well. For assumption (1), dimensional analysis using the Biot theory (Biot 1956a,b) has revealed that the response of saturated rocks to seismic waves is dependent on dimensionless frequency (Li 2020a), where and are water density, permeability, water viscosity and angular frequency, respectively. Low frequency ( ) will cause to tend to zero.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The elastic model in the Appendix has two assumptions: (1) the rocks are undrained during the passage of a transient Rayleigh wave such that the Gassmann (1951) equation is applicable; (2) the well head adequately represents fluid pressure in the matrix surrounding the well. For assumption (1), dimensional analysis using the Biot theory (Biot 1956a,b) has revealed that the response of saturated rocks to seismic waves is dependent on dimensionless frequency (Li 2020a), where and are water density, permeability, water viscosity and angular frequency, respectively. Low frequency ( ) will cause to tend to zero.…”
Section: Methodsmentioning
confidence: 99%
“…Strictly speaking, aquifer storativity (specific storage) is defined as , where and are porosity, compressibility coefficients of water, skeleton and solid material, respectively (Li et al 2020a). As a reminder, this expression is slightly more accurate than the one in Domenico & Schwartz (1997) in considering the compressibility of solid material.…”
Section: Problem Identificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Biot (1956aBiot ( , 1956b theory was more accurate than the storativity equation for water-pressure diffusion in hydrogeology; the storativity equation is the governing equation of water pressure in aquifers with the consideration of water compressibility and skeleton compressibility (Domenico & Schwartz, 1997;Li et al, 2020a). Under the assumptions of low frequency and zero confining pressure, Li et al (2020a) showed that Biot theory can be simplified to the storativity equation. Biot (1956a) used Darcy permeability (k D ) in hydrogeology and static fluid viscosity (μ) in fluid mechanics to quantify viscous stress between solid and fluid.…”
Section: Introductionmentioning
confidence: 99%